FIGURE 54. A–E, Cyclograpsus integer H. Milne Edwards, 1837. A, B in Brachyuran crabs (Crustacea, Decapoda) from the remote oceanic Archipelago Trindade and Martin Vaz, South Atlantic Ocean - TAVARES, MARCOS; MENDONÇA, JOEL BRAGA DE JR. (Zenodo, 2022)
FIGURE 54. A–E, Cyclograpsus integer H. Milne Edwards, 1837. A, B, Juvenile female, cl 5.9 mm, cw 7 mm (MZUSP 42516). C–E, Male, cl 8.4 mm, cw 9.1 mm (MZUSP 42516). Scales: 2 mm. Photographs by P.A. Hernáez Bové. Published as part of TAVARES, MARCOS & MENDONÇA, JOEL BRAGA DE JR., 2022, Brachyuran crabs (Crustacea, Decapoda) from the remote oceanic Archipelago Trindade and Martin Vaz, South Atlantic Ocean, pp. 1-129 in Zootaxa 5146 (1) on page 104, DOI:10.11646/zootaxa.5146.1.1, http://zenodo.org/record/7626155